Dataset for the study: Hedonic, gastrointestinal, and acute responses to pre-workout protein intake - Portuguez Molina, Priscilla (2025)
A complete dataset is presented as collected and analyzed for the study on hedonic and gastrointestinal acute responses to pre-workout protein intake. Participants had two identical sessions (milk and yogurt); they completed a hedonic scale only after product ingestion and a gastrointestinal sympoms questionnaire at four points in time: before ingestion of the product, after the ingestion, in the middle of the exercise session (mid session), and at the end of the session. The dataset supports a manuscript currently under review in the Nutrients journal.